2018
DOI: 10.1002/nur.21902
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐reported symptoms improve prediction of acute coronary syndrome in the emergency department

Abstract: Early diagnosis is critical in the management of patients with acute coronary syndrome (ACS), particularly ST-elevation myocardial infarction (STEMI), because effective therapies are time-dependent. Aims of this secondary analysis were to determine: (i) the prognostic value of symptoms for an ACS diagnosis in conjunction with electrocardiographic (ECG) and troponin results; and (ii) if any of 13 symptoms were associated with prehospital delay in those presenting to the emergency department (ED) with potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 42 publications
1
8
0
1
Order By: Relevance
“…For instance, a recent prospective study by Zègre-Hemsey et al examined delay > 3 h in a cohort of 590 non-ACS controls and 474 ACS cases (21). They found that 63% of non-ACS patients and 49% of ACS patients had a delayed presentation > 3 h (21). When compared to our study, we found an overall prevalence of > 2 h delay in 46% of patients in our cohort (Figure 1).…”
Section: Prevalence Of Delay In Seeking Caresupporting
confidence: 48%
See 2 more Smart Citations
“…For instance, a recent prospective study by Zègre-Hemsey et al examined delay > 3 h in a cohort of 590 non-ACS controls and 474 ACS cases (21). They found that 63% of non-ACS patients and 49% of ACS patients had a delayed presentation > 3 h (21). When compared to our study, we found an overall prevalence of > 2 h delay in 46% of patients in our cohort (Figure 1).…”
Section: Prevalence Of Delay In Seeking Caresupporting
confidence: 48%
“…However, it is worth noting that delay has been defined differently throughout literature. For instance, a recent prospective study by Zègre-Hemsey et al examined delay > 3 h in a cohort of 590 non-ACS controls and 474 ACS cases (21). They found that 63% of non-ACS patients and 49% of ACS patients had a delayed presentation > 3 h (21).…”
Section: Prevalence Of Delay In Seeking Carementioning
confidence: 99%
See 1 more Smart Citation
“…The clinical characteristics of ACS, including ST segment elevation of myocardial infarction (STEMI), non-STEMI, and unstable angina, is known to be widespread causes for disability and mortality [ 1 ]. Life-saving therapies for ACS patients are strongly dependent on early and prompt identification of signs and symptoms, whereas atypical appearance of ACS symptoms may lead to delayed diagnosis, delayed care, less evidence-based approaches, and increased morbidity and mortality [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…In patients with CAD, the prevalence of moderate to severe fatigue has been reported to be as high as 39% during cardiac rehabilitation (CR), remaining up to 28% after 1 year (van Geffen et al, 2015). Meanwhile, mental fatigue is considered a risk factor for the development of heart diseases (Guan et al, 2017), while unusual fatigue is a strong predictor of longer prehospital delay (Zègre-Hemsey et al, 2018), poor health-related outcomes, and increased mortality (Irvine et al, 1999). Considering fatigue within the context of emotional stress, it may not only be a distressing symptom itself but also may play an important role in determining the effort and motivation to perform a task (Wright, 2014), and so in turn may shape variations of cardiovascular response to stress (Wright, 2009).…”
Section: Introductionmentioning
confidence: 99%